Langage et système des lois suisses - Dessemontet, François (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
This paper addresses the issue of a systematic approach to the drafting of legislation, in the light of Swiss experience. Starting from a brief survey of inflationary tends in the production of Legislative material, the author brings out the mutually reinforcing interplay between these tends and a widening lack of consensus about the contents and enforceability of legislation. While such factors hardly favour systematic lawmaking, a number of institutional features in the Swiss federal legislative process help maintain the quality of legislative instruments — namely the very length of the process, the bicameralism, the plurality of official languages, and the subjection of laws to the referendum procedure. Further, the practice of Swiss Legislators shows concern for the preservation of systematic unity. Thus, the federal department of Justice has devised a set of Principles of legislative drafting, supplemented by a checklist that can be applied to any draft legislative instrument. In a number fields where lawmaking authority vests in the cantons rather than in the Confederation, federal authorities have drafted model laws in the hope of promoting uniformity between cantonal legislation. In.other fields, where law-making authority has been given to the Confederation, federal legislation has sometimes been limited to a basic law, containing broad provisious only leaving details to be filled in by each of the cantons. The technique of codification, by contrast, has not been resorted to since the major achievements in civil and criminal law during the first half of this century. Finally, Swiss legislative draftsmen, both federal and cantonal, have been concerned lately with the improvement of drafting and style, as is shown by the recent spread of guidelines, instructions and even laws on the subject.